High-energy radiation from T-Tauri stars - Romero, Gustavo Esteban (2011)
T Tauri stars are young, low mass, pre-main sequence stars surrounded by an accretion disk. These objects present strong magnetic activity and powerful magnetic reconnection events. Strong shocks are likely produced in the stellar magnetosphere by such events and charged particles accelerated up to relativistic energies. We present a simple model for the non-thermal radiation generated by high-energy particles in T Tauri stars. We discuss whether this emission is detectable at high energies with the available gamma-ray telescopes.